Anti-harassment training programmes in the RCMP: Is organizational transformative learning possible? - Karen E. Yong (Adult Education Research Conference, 2020)
Examining a complex hierarchical law enforcement organization mandated anti-harassment (AH) training programmes. A sample of the RCMP revealed bullying negative behaviours occurring at 19% across study group (n=237). Mix-method approach using Kirkpatrick Evaluation, OCAI and NAQ-R provided insights into the correlation of training to organizational stated culture goals. More males reported being bullying (25%) No overt bullying reported by female respondents however, subtle bullying remains. All training materials aligned with organizational mission, vision and strategic goals. Curricula was clear however a gap exists between formal training and applied learning as evidenced by quantitative assessments. The NAQ-R (Cronbach alpha 0.777) indicates the presence of bullying but not at toxic levels. The OCAI highlights an overly hierarchical quadrant fulfilling market needs at the expense of clan and adhocracy quadrants. These findings support previous qualitative studies and employee engagement results. The leadership has choices to move forward and strengthen its AH training efforts.